1980
DOI: 10.2134/agronj1980.00021962007200030009x
|View full text |Cite
|
Sign up to set email alerts
|

Double and Monocropped Wheat and Soybeans Under Different Tillage and Row Spacings1

Abstract: In wheat [Triticum aestivum (L.) Thell] producing regions with adequate frost‐free days to permit double‐cropping, water is often the most limiting factor in producing the second crop. To more fully utilize climatic resources and land after the harvest of wheat grain, a field study was conducted on a Wynona silty clay loam (Cumulic Haplaquolls) to analyze the effects of tillage and row spacings on soil water content and yields of monocropped (MC) and double‐cropped (DC) wheat and soybeans [Glycine max (L.) Mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…These soybean, then, efficiently utilized water deeper in the profile. Crabtree and Rupp ( 1980) also concluded that the double-cropping of wheat and soybean used water stored in a 120-cm profile more efficiently than the monocropping of either crop. Cropping system had no significant effect upon extractable water in the 76-cm soybean plots ( Table 2).…”
Section: Interactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…These soybean, then, efficiently utilized water deeper in the profile. Crabtree and Rupp ( 1980) also concluded that the double-cropping of wheat and soybean used water stored in a 120-cm profile more efficiently than the monocropping of either crop. Cropping system had no significant effect upon extractable water in the 76-cm soybean plots ( Table 2).…”
Section: Interactionsmentioning
confidence: 99%
“…This shading likely slowed soil evaporation. Crabtree and Rupp (1980) found that an extensive crop canopy limited evaporative water loss. Crop canopy enlargement does, however, increase soil water loss due to plant transpiration (Taylor and Ashcroft, 1972).…”
Section: Main Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Grower interest has increased dramatically in crops serving as alternatives to complement winter wheat in continuous, winter wheat monocrop areas. Reasons may be agronomic, environmental, or economic (2,3,4,5,18). Soybean can be produced as an early-season or doublecrop with winter wheat in cropping systems, representing multiple cropping and increasing the number of crops harvested per unit area of land for a given time period.…”
Section: Introductionmentioning
confidence: 99%